Comparative transcriptome analysis unveiling reactive oxygen species scavenging system of Sonneratia caseolaris under salinity stress - Zhou, Yan; Wen, Lizhen; Liao, Lixian; Lin, Shuangmei; Zheng, Enting; Li, Yin; Zhang, Ying (Frontiers in Plant Science, 2022)
Many mangrove forests have undergone major changes due to human activities and global climate change in the world. Sonneratia caseolaris is common in the inner mangroves and extends inland along tidal creeks as far as the influences of salinity extends. This study investigates the physiological and molecular responses of S. caseolaris plants to salt stress by analyzing their antioxidant defense capacity, including their differentially expressed genes (DEGs) under similar salt stress conditions. Salt treatment significantly affected the osmoprotectants and lipid peroxidation in S. caseolaris seedlings, which increased proline content and decreased malonaldehyde (MDA) content. Antioxidant enzymatic activity increased significantly following 30‰ NaCl treatment. Transcriptome analysis following de novo assembly showed that salt stress induced differentially expressed genes involved in the metabolic and biological regulation processes of reactive oxygen species (ROS). In addition, the transcription levels of genes that mediate auxin and ethylene transport or signaling were altered. Under salt stress, ROS scavenging-genes and the MYB transcription factor were upregulated. This study identified important pathways and putative genes involved in the salt tolerance of S. caseolaris and provided suggestions to elucidate the mechanisms of salt tolerance, as well as the utilization of salt tolerance genes in S. caseolaris.